Mesoscale en échelon precipitation radar patterns over the Hebrides, northwest Scotland, on 9 October 2022. (7th December 2022) - Graham, Edward; Smart, David; Kidd, Chris; Blackmore, Thomas
Abstract : An intense narrow cold‐frontal rain band (NCFR) passed over the Hebrides of northwest Scotland on the morning of 9 October 2022. As the NCFR approached and crossed over the Isles, it developed a pronounced en échelon wavelike pattern of precipitation elements. A vertically pointing Metek 24GHz micro rain radar (known as LERADAR), operated by the University of the Highlands and Islands at Lews Castle, Stornoway, also recorded the passage of the NCFR, capturing its features at almost microscale resolution.